6m+4=5m-1

Simple and best practice solution for 6m+4=5m-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6m+4=5m-1 equation:


Simplifying
6m + 4 = 5m + -1

Reorder the terms:
4 + 6m = 5m + -1

Reorder the terms:
4 + 6m = -1 + 5m

Solving
4 + 6m = -1 + 5m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-5m' to each side of the equation.
4 + 6m + -5m = -1 + 5m + -5m

Combine like terms: 6m + -5m = 1m
4 + 1m = -1 + 5m + -5m

Combine like terms: 5m + -5m = 0
4 + 1m = -1 + 0
4 + 1m = -1

Add '-4' to each side of the equation.
4 + -4 + 1m = -1 + -4

Combine like terms: 4 + -4 = 0
0 + 1m = -1 + -4
1m = -1 + -4

Combine like terms: -1 + -4 = -5
1m = -5

Divide each side by '1'.
m = -5

Simplifying
m = -5

See similar equations:

| -2[8-5(2-3x)-7x]=4(x+9) | | x+-0.05x+11.95x=1-1 | | X=(2x^2+3x-6)+(x^2-18x+6) | | 4x^2+3x-6=0 | | 6x^2-6x+10=2x^2-2x+25 | | x-0.5(0.1x-2)=1+11.95x | | -9x+3x=-24 | | 8x(3x+2)=-5(2-x)+3 | | 1270=.15x | | -5x-13x+3x=-25 | | -5x-13x+3x=25 | | 2x+y-4= | | 3+5m-4-8m=-8(m-3)+2(m-8) | | 8-3=5 | | 2+2-2=2+2-2+2 | | 24*x=96 | | 24xy=96 | | y(y+1)=20 | | (x+5)(x+5)=16 | | 9(c-1)=6(b+2)-a | | 77.94-5.8+201.681= | | 2x^2-36x+162=32 | | 10a^2-27ab+5b= | | 9(n-1)=6(n+2) | | x-7=3x | | 3(x+4)=(3x+12) | | 9x-1(4x-1)=2 | | 9x+3(-3x-5)=-12-3x | | 8x-7-7x-7=8x-7x-17 | | -7b+4+5b=-3b+9 | | 2(4x+7)=3+2x+2 | | 4x^2+2x-6= |

Equations solver categories